Length–weight relationships of freshwater fishes from the western part of Anatolia, Turkey. (12th September 2012) - Gaygusuz, Ö.; Aydın, H.; Emiroğlu, Ö.; Top, N.; Dorak, Z.; Gaygusuz, Ç. G.; Başkurt, S.; Tarkan, A. S.
Summary Length–weight relationships were calculated for nine freshwater fish species belonging to two families using 1020 specimens from 15 water sources in the western part of Anatolia, Turkey. This study is the first reference on length–parameters for these species, eight of which are endemic, and with new maximum length records for three of the species.